2020
DOI: 10.3389/fpls.2020.01292
|View full text |Cite
|
Sign up to set email alerts
|

Water Deficits Do Not Improve Fruit Quality in Grapevine Red Blotch Virus-Infected Grapevines (Vitis vinifera L.)

Abstract: Although deficit irrigation is used to improve fruit quality in healthy grapevines, it can potentially amplify negative effects of viral disease and reduce fruit quality in Grapevine Red Blotch Virus (GRBV) infected grapevines. Therefore, a 2-year field experiment was conducted to understand the interaction between GRBV infection and water deficits on disease development and vine physiology. Well-watered (WW) vines were irrigated at 100% of estimated crop evapotranspiration (ET c), while water deficit (WD) vin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 56 publications
(85 reference statements)
2
11
0
Order By: Relevance
“…Despite the fact that there were no non-infected vines in this study, there was nevertheless a significant increase in berry TSS of approximately 1 to 3 °Brix in the SUPP irrigation vines. The °Brix improvement observed in this study is within the range or greater than some reported reductions in TSS as a result of GRBV (Martínez-Lüscher et al 2019, Levin andKC 2020). While berry TSS is a useful technological marker for important production decisions such as harvest, the amount of sugar per berry is perhaps more indicative of vine carbon metabolism and more directly demonstrates the overall impact of supplemental irrigation on vine physiology.…”
Section: Irrigation Improved Carbon Assimilation and Translocation By Elevating Water Statussupporting
confidence: 73%
See 4 more Smart Citations
“…Despite the fact that there were no non-infected vines in this study, there was nevertheless a significant increase in berry TSS of approximately 1 to 3 °Brix in the SUPP irrigation vines. The °Brix improvement observed in this study is within the range or greater than some reported reductions in TSS as a result of GRBV (Martínez-Lüscher et al 2019, Levin andKC 2020). While berry TSS is a useful technological marker for important production decisions such as harvest, the amount of sugar per berry is perhaps more indicative of vine carbon metabolism and more directly demonstrates the overall impact of supplemental irrigation on vine physiology.…”
Section: Irrigation Improved Carbon Assimilation and Translocation By Elevating Water Statussupporting
confidence: 73%
“…Ultimately, the most significant result from this study was an improvement in TSS in fruit from vines that received supplemental irrigation. Studies of the impact of GRBV on vine physiology and fruit composition indicate that a reduction in TSS is the most consistent effect of the virus (Levin and KC 2020). Despite the fact that there were no non-infected vines in this study, there was nevertheless a significant increase in berry TSS of approximately 1 to 3 °Brix in the SUPP irrigation vines.…”
Section: Irrigation Improved Carbon Assimilation and Translocation By Elevating Water Statusmentioning
confidence: 55%
See 3 more Smart Citations